Hubungan Pengetahuan Komunitas Pendengar Terhadap Iklan SmartFren Di Radio Elgangga Dengan Minat Beli - Dhefine Armelsa; Faqihar Risyan; Susilowati (LPPM Universitas Bina Sarana Informatika, 2021)
The communication carried out by radio is mass communication, namely communication to many people using media and the communication style must be in the form of personal or interpersonal communication because radio listeners. One of the main options or options for using radio for large companies is to promote their goods or services as a sales promotion (marketing promotion). These companies try to advertise their products as attractively as possible. This study aims to determine the relationship of knowledge from a listener community to SmartFren advertisements on Elgangga Radio with buying interest. Various concepts, programs, and Marketing Public Relations strategies are needed to attract as many consumers or visitors as possible, so that the company continues to grow and is able to face its competitors by providing satisfaction from its customers. The method used in this study is a survey with a quantitative approach, and knowledge (variable X) and buying interest (variable Y) using a Likert scale technique in scoring used in the questionnaire. The results and conclusions show that the Marketing Public Relations strategy that has been carried out is going quite well, the management designs every strategy and programs that are made by taking into account market segmentation and consumer targeting, so that in making strategic programs it fits the wishes of the visitors. Keywords : Marketing Public Relations Strategy, Knowledge, Radio, Buying Interest